Feeding habits of the spider crab Libinia spinosa H. Milne Edwards, 1834 (Decapoda, Brachyura) in Ubatuba Bay, São Paulo, Brazil - Barros, Samara de Paiva; Cobo, Valter Jose; Fransozo, Adilson [UNESP] (Inst Tecnologia Parana, 2008)
The main goal of this study was the identification of the items of the diet of the L. spinosa, based on the stomach contents analysis. The crabs were obtained from Ubatuba region north-eastern shore of São Paulo State. In the laboratory, all the individuals were dissected, the stomach was retreated and fixed in 10% formaline. The alimentary items were identified under stereomicroscope and analysed by the method of Frequency of Occurrence. A total of 194 stomachs was analysed and nine alimentary items were obtained. Unindentified material was found in 98% of analysed stomach and poriferan were present in less then 1% of stomachs. These results pointed a diversified diet explored by this crab, as well as the employment of some different methods for food intake. This suggested that these crabs could occupy different position in the trophic chain.

O objetivo deste trabalho é identificar os itens alimentares que compõem a dieta de L. spinosa, por meio da análise do conteúdo estomacal. Os caranguejos foram coletados no litoral norte paulista (23º25’S–45º00’W). No laboratório, todos indivíduos foram dissecados, os estômagos foram retirados e fixados em formol 10%. Os itens alimentares foram identificados sob estereomicroscópio, sendo que para a análise foi utilizado o método Freqüência de Ocorrência. Foram analisados 194 estômagos, nos quais foram encontrados nove itens alimentares. A maior freqüência foi para material não identificado, ocorrendo em 98% dos estômagos analisados e Porifera foi o item com a menor freqüência, ocorrendo em menos de 1% dos estômagos. Com base nos resultados obtidos, sugere-se que o caranguejo L. spinosa apresenta uma dieta diversificada, sugerindo a utilização de diferentes métodos para a obtenção de alimento e por conseqüência podendo ocupar vários níveis na cadeia trófica.
Keywords: stomach contents; alimentary itens; spider crab